The Homes of our heroes [videorecording] - Medina, Susan Calo.; Quintos, Floy.; GMA-7 (Television station : Quezon City).; Philippines. Department of Tourism; Philippines. National Commission for Culture and the Arts.; Travel Time (Television program). (Manila Travel Time, 1995)
Journeys through the homes of our Philippine heroes.
VHS.
Editor, Robert W. Razon, Jr.
Keywords: Architecture, Domestic -- Philippines; Dwellings -- Philippines; Historic building -- Philippines